Transformation of Teaching Competencies of Islamic Religious Education Students through the Integration of Reflective Videos in Microteaching - Siti Afifatun; Alfira Mersania Shintia; Aulia Tanzania; Agung Agus Revaldi; Amelia Handayani (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study examines the implementation of micro teaching practice among students of the Islamic Religious Education (PAI) Study Program through an observational activity conducted by four sixth-semester students at STAI Ibnu Rusyd Kotabumi in the 2026/2027 academic year. As observers, we directly monitored the micro teaching practice carried out by fellow students as part of efforts to develop the teaching competencies of prospective PAI teachers. The observation was conducted using a Classroom Action Research (CAR) approach to document and analyze the development of teaching competencies, encompassing mastery of subject matter, pedagogical skills, and effective communication. Data were collected through structured observation and analysis of written reflection documents, then analyzed using a descriptive qualitative method. The results of the observation indicate meaningful development in the teaching competencies of students engaged in micro teaching practice. The three main dimensions observed were mastery of subject matter, pedagogical skills, and effective communication. This study has strategic implications for the development of micro teaching practice programs at STAI Ibnu Rusyd Kotabumi as part of the preparation of competent and professional prospective PAI teachers.